Quantitative approaches to the Russian language - Kopotev, Michail Vjačeslavovič,Ljaševskaja, Olʹga N.,Mustajoki, Arto S. (Routledge Taylor & Francis Group, 2018)
Russian challenges for quantitative research / Mikhail Kopotev, Olga Lyashevskaya, Arto Mustajoki –
Includes bibliographical references and index
Keywords: Russian language; Computational linguistics; Quantitative research